LSSA: A Protective Shared Data Communication Mechanism in Cloud Environment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Users can access shared data warehouses using a cloud infrastructure. It is important to verify the data successfully to ensure mutual data integrity. The accuracy checking of the shared data is carried out by an examination system that encourages Group members to alter data, but this method leads to complicated estimates for the Group members. The monitoring method of the assigned agent estimates the group members lightly, but lacks the safety threats between the group members and their agents. With the implementation of Hash graph technology and the development of a management Third Party Medium (TPM) approach, a Lightweight Safe Cloud Storage Audition System (LSSA) is suggested, achieving group security protection and a lightweight group measurement. In the meantime, the TCP Sliding Fan Technology incorporates a simulated TPM pool with interconnected features to enhance support for the handler. We test our method in numerical analysis and tests, which prove that our system provides the groups with lightweight computing and ensures the safety data evaluation process.